2021
DOI: 10.3389/fphys.2021.674197
|View full text |Cite
|
Sign up to set email alerts
|

Location of Parasympathetic Innervation Regions From Electrograms to Guide Atrial Fibrillation Ablation Therapy: An in silico Modeling Study

Abstract: The autonomic nervous system (ANS) plays an essential role in the generation and maintenance of cardiac arrhythmias. The cardiac ANS can be divided into its extrinsic and intrinsic components, with the latter being organized in an epicardial neural network of interconnecting axons and clusters of autonomic ganglia called ganglionated plexi (GPs). GP ablation has been associated with a decreased risk of atrial fibrillation (AF) recurrence, but the accurate location of GPs is required for ablation to be effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 117 publications
(162 reference statements)
3
9
0
Order By: Relevance
“…One open question is still the possibility of obtaining repolarization times from EGMs as repolarization of the cardiac tissue plays a pivotal role for the initiation of arrhythmias ( Rivaud et al, 2021 ). From simulations of atrial electrophysiology, Celotto et al (2021) proposed a method to detect areas of parasympathetic innervation from the amplitude of the repolarization EGM. Verrier et al (2016) showed that repolarization times can be recovered from EGMs for both the atrium and the ventricle in a controlled clinical environment.…”
Section: Research Gaps and Potential Future Developmentsmentioning
confidence: 99%
“…One open question is still the possibility of obtaining repolarization times from EGMs as repolarization of the cardiac tissue plays a pivotal role for the initiation of arrhythmias ( Rivaud et al, 2021 ). From simulations of atrial electrophysiology, Celotto et al (2021) proposed a method to detect areas of parasympathetic innervation from the amplitude of the repolarization EGM. Verrier et al (2016) showed that repolarization times can be recovered from EGMs for both the atrium and the ventricle in a controlled clinical environment.…”
Section: Research Gaps and Potential Future Developmentsmentioning
confidence: 99%
“…Many modelling and experimental studies have demonstrated that fibrosis results in increased conduction anisotropy and the introduction of substantial transverse conduction delay, with longitudinal conduction largely unchanged [1,16,17,36]. Increased collagen deposits preferentially occur between myocytes in the lateral direction, resulting in a collection of largely separated myofibre bundles [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Many modelling and experimental studies have demonstrated that fibrosis results in increased conduction anisotropy and the introduction of substantial transverse conduction delay, with longitudinal conduction largely unchanged [1,16,17,36].…”
Section: Model Of Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, current randomized studies showed no difference in recurrence rate as compared with PV isolation only ( 17 ). Ganglion plexi are positioned mostly within the epicardial fat pad and are composed of various ganglia and interconnected axons ( 19 , 23 ). In the atrium, ganglionic plexi are mostly located in the posterior wall of the left atrium, and ablation of the ganglion plexi has been proposed as one of the strategies ( 3 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%